Pengaruh Kepuasan Konsumen Terhadap Keputusan Pembelian Pada Toko XYZ Pekanbaru - A’inun , Nisa; Hendra, Teguh (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This research will be carried out at the XYZ Pekanbaru Shop. The purpose of this research is to determine the influence of consumer satisfaction on purchasing decisions at the XYZ Pekanbaru store. The sample in this study was 92 respondents using the Slovin formula. In this research the sample method uses census techniques. Data analysis in this research uses descriptive and quantitative methods. Based on the results of the research analysis, it was found that Consumer Satisfaction has a significant influence on Purchasing Decisions at the XYZ Pekanbaru Store based on tcount = 6.577 > ttable = 1.98667. The results of simple linear regression show that the regression equation is Y =31.140 + 0.738X, this means that the research results are the same as the research hypothesis. The R2 value is 0.344, which means that the influence of Consumer Satisfaction has a significant influence on Purchasing Decisions at the XYZ Pekanbaru Store, which is 32.5%, while 67.5% is influenced by other variables not studied in this research.